(untitled) (INTERNATIONAL CONFERENCE ON ADVANCE SCIENCE AND TECHNOLOGY, 2026)
This article analyzes the organizational, psychological, financial, and cultural barriers that hinder innovation in traditional management structures. Using the example of Uzbekistan’s companies, the impact of bureaucratic hierarchy, resistance to change, resource constraints, and short-term thinking on innovative potential is examined. The article proposes practical strategies for overcoming these barriers and a pedagogical-managerial model for building an innovative organizational culture.